The Nature of Fear - Blumstein, Daniel T. (Harvard University Press, 2020)
A leading expert in animal behavior takes us into the wild to better understand and manage our fears.Fear, honed by millions of years of natural selection, kept our ancestors alive. Whether by slithering away, curling up in a ball, or standing still in the presence of a predator, humans and other animals have evolved complex behaviors in order to survive the hazards the world presents. But, despite our evolutionary endurance, we still have much to learn about how to manage our response to danger.For more than thirty years, Daniel Blumstein has been studying animals' fear responses. His observations lead to a firm conclusion: fear preserves security, but at great cost. A foraging flock of birds expends valuable energy by quickly taking flight when a raptor appears. And though the birds might successfully escape, they leave their food source behind. Giant clams protect their valuable tissue by retracting their mantles and closing their shells when a shadow passes overhead, but then they are unable to photosynthesize, losing the capacity to grow. Among humans, fear is often an understandable and justifiable response to sources of threat, but it can exact a high toll on health and productivity.Delving into the evolutionary origins and ecological contexts of fear across species, The Nature of Fear considers what we can learn from our fellow animals--from successes and failures. By observing how animals leverage alarm to their advantage, we can develop new strategies for facing risks without panic.